2015
DOI: 10.1007/s00374-015-1013-4
|View full text |Cite
|
Sign up to set email alerts
|

Land-use intensity and soil properties shape the composition of fungal communities in Mediterranean peaty soils drained for agricultural purposes

Abstract: Anthropogenic effects on soil fungi have been poorly investigated in peaty soils, where they have a crucial role in the maintenance of soil fertility and in the regulation of nutrient cycles. In this study, we assessed the effects of landuse intensification on the composition of fungal communities in Mediterranean peaty soils drained for agricultural purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 86 publications
3
19
1
Order By: Relevance
“…Among the abiotic factors that can have relevant roles in driving AMF communities are soil moisture (75), rainfall patterns, and geographical distance (40,76). There is no doubt that soil type has a role in the AMF distribution (10,34,35,40,(77)(78)(79)(80), and our work also demonstrated that soil type is a major factor driving AMF assemblages, after elimination of the host factor and other environmental variables not related to soil characteristics. Although individual soil characteristics have been reported to play important roles in AMF community structure and composition (7,11,13,40,42,78,(81)(82)(83), very limited data sets regarding soil characteristics were used in these studies, and the relative incidences of each soil property determined after complete soil characterization have not been reported previously.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Among the abiotic factors that can have relevant roles in driving AMF communities are soil moisture (75), rainfall patterns, and geographical distance (40,76). There is no doubt that soil type has a role in the AMF distribution (10,34,35,40,(77)(78)(79)(80), and our work also demonstrated that soil type is a major factor driving AMF assemblages, after elimination of the host factor and other environmental variables not related to soil characteristics. Although individual soil characteristics have been reported to play important roles in AMF community structure and composition (7,11,13,40,42,78,(81)(82)(83), very limited data sets regarding soil characteristics were used in these studies, and the relative incidences of each soil property determined after complete soil characterization have not been reported previously.…”
Section: Discussionsupporting
confidence: 55%
“…PCRbased methods have been used to detect AMF in plant roots and in soil in numerous studies in natural and seminatural ecosystems, including grasslands (26), wetlands (27), agricultural ecosystems (12), urban soils (28), semiarid shrubland (29, 30), and a temperate forest (31). Recently, some investigations have incorporated fungal DNA extraction from soil in addition to root extractions (9,(32)(33)(34)(35) as tools to describe the total AMF soil diversity, including actively functioning fungal taxa as well as dormant spores.…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Explanations for such different effects could be (1) the host plants that were tested were different, C. dactylon in this study was a flooding-tolerant herbaceous plant with adventitious roots and aerenchyma, as AMF diversity was affected by the host plant identity [60,61]; (2) the land-use intensity was different, as the AMF diversity was affected by land-use intensity [67]. Thus, such effects may depend on region-specific factors, including host characteristics, environmental conditions, and land-use intensity [29,68,69]. On the one hand, this present study did show a higher AMF richness and diversity in the rhizosphere soils than in roots, which is consistent with findings from Pellegrino et al [70] and Moora et al [67].…”
Section: Differences In Amf Colonization Diversity and Community In mentioning
confidence: 99%
“…High-intensity land uses analyzed previously were often associated with a reduction in AMF abundance and/or diversity (e.g., Van Geel et al 2015;Verbruggen et al 2015;Ciccolini et al 2015;Spurgeon et al 2013;Borriello et al 2012;Lumini et al 2010). AMF communities were characterized in spring and autumn 2011 on the basis of 454 sequencing of the internal transcribed spacer 2 (ITS2) rDNA region.…”
Section: Introductionmentioning
confidence: 99%